O cuidado e a ética do cuidado: um diálogo entre Leonardo Boff, Carol Gilligam e Nel Noddings - Setúbal, Hilana Cristina Rocha (2010)
To elucidate the important contribution of care ethics in improving human relations and social intimates, this work reveals the fragility and lack of ethics on the formation of a just society, equal, peaceful and caring. To this end, we study on the moral development of men and women, warning of the natural differences between the sexes, which change for both the way of seeing life and live it - which does not imply inferiority to some genres. From this study it is clear that the natural care is innate to humans, it provides a tendency to act for the good of all life forms and nature as a whole. But it is evident here a greater sensitivity of women to such care because they possess perception and more emotion than men, which make them more participatory and involved in relationships. This greater openness to care found in women, due in part to the strong and lasting relationship with their mothers. Thus is revealed the power that women have to positively change the direction of human relationships, providing careful with your example, protective and caring, the awakening of a new and comprehensive ethics - opens to the truth, and features especially for affections. Therefore, the care ethics arises from the life experiences of women and aims, through them, to join the men's morality in order to bring out the relevant fact of interdependence between human beings, of human fragility and the need for relationships to the fullness of life